The Effects of the COVID-19 Pandemic Lockdown on Eating, Body Image, and Social Media Habits Among Women With and Without Symptoms of Orthorexia Nervosa - Gobin, Keisha C.; Mills, Jennifer S.; McComb, Sarah E. (Frontiers in Psychology, 2021)
The COVID-19 pandemic is negatively impacting people’s mental health worldwide. The current study examined the effects of COVID-19 lockdown on adult women’s eating, body image, and social media habits. Furthermore, we compared individuals with and without signs of orthorexia nervosa, a proposed eating disorder. Participants were 143 women, aged 17-73 years (M = 25.85, SD = 8.12), recruited during a COVID-19 lockdown in Canada from May-June 2020. Participants completed self-report questionnaires on their eating, body image, and social media habits during the pandemic. The Eating Habits Questionnaire (EHQ) assessed symptoms of orthorexia nervosa. Compared to the period prior to lockdown, women with higher total orthorexia nervosa scores reported eating a lot more than usual, feeling greater pressure to diet and lose weight, thinking about food more often than usual, experiencing greater weight gain, and perceiving more pressure from social media specifically to lose weight and to exercise, compared to their healthy counterparts. We examined associations between individual EHQ subscales and perceived changes to eating and weight. Women who scored high on EHQ-Problems reported seeing more weight loss content on their social media than those who reported fewer orthorexia nervosa symptoms. Conversely, those who scored low on EHQ-Feelings reported feeling a lot less pressure to lose weight, somewhat less or a lot less pressure to lose weight or to exercise from social media specifically, and trended towards less laxative use during lockdown, compared to those who scored higher on orthorexia nervosa. And those who scored low on EHQ-Knowledge reported feeling somewhat less or a lot less pressure to lose weight than those who reported more orthorexia nervosa symptoms. Together, the findings suggest that women with symptoms of orthorexia nervosa are experiencing an exacerbation of disordered eating thoughts and behaviours during COVID-19, and that social media may be a contributing factor.